Water production function and optimal irrigation programme for drip irrigated castor (Ricinus communis L.): WATER PRODUCTION FUNCTION AND OPTIMAL IRRIGATION PROGRAMME FOR CASTOR - B R KUMAR; V PRAVEEN RAO; V RAMULU; M UMA DEVI; K AVIL KUMAR (Journal of Oilseeds Research, 2014)
Water shortage for crop production necessitates adequate knowledge of the crop water production function to make decisions on water allocation for optimum returns from castor crop under surface drip irrigation. The study was conducted in rabi 2009-10 at Agricultural college farm, Rajendranagar, Hyderabad. The different drip irrigation schedules at 40, 60 and 80 per cent pan evaporation replenishment levels either kept constant throughout the crop life or combinations at vegetative, flowering and development stages were compared with surface check basin at (0.8 IW/CPE ratio) irrigation. The results showed that drip irrigation at 0.6 Epan replenishment up to flowering and 0.8 Epan later on registered comparable seed yields with drip irrigation scheduled at either at 0.6 or 0.8 Epan and was significantly superior over other treatments and the best fit water production function was quadratic (R2= 0.99). The optimum quantity of water (ETc) for maximum net returns under prevailing prices (water and castor @ `10 and 30 ha/mm and kg/ha, respectively) was 381.4 ha mm with a resultant seed yield of 3611 kg/ha. The gross returns, net returns and net return/rupee invested varied from ` 72194 to 144447/ha, ` 36808 to 108018/ha and 1.040 to 3.049, respectively.